2017
DOI: 10.1371/journal.pone.0186712
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic trauma now and then: A 10 year experience from 16,773 severely injured patients

Abstract: Background and purposeThoracic trauma remains to be a relevant injury to the polytraumatised patient. However, literature regarding how far changes in clinical guidelines for pre- and in-hospital trauma management and diagnostic procedures affect the outcome of multiple injured patients with severe chest injury during a long-term observation period is sparse.MethodsMultiple traumatised patients (age≥16y) documented in the TraumaRegister DGU® (TR-DGU) from January 1st 2005 to December 31st 2014 with severe ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 66 publications
(70 reference statements)
5
41
0
1
Order By: Relevance
“…Increases in the incidence of thoracic injuries have been reported in prior studies, and were purported to be due to the increased use of CT 24. Chest radiography, previously the mainstay investigation, has a low sensitivity for thoracic injuries25 and the more widespread use of CT among the trauma population could have resulted in an increased rate of detection of previously missed or underestimated injuries 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in the incidence of thoracic injuries have been reported in prior studies, and were purported to be due to the increased use of CT 24. Chest radiography, previously the mainstay investigation, has a low sensitivity for thoracic injuries25 and the more widespread use of CT among the trauma population could have resulted in an increased rate of detection of previously missed or underestimated injuries 24…”
Section: Discussionmentioning
confidence: 99%
“…Chest radiography, previously the mainstay investigation, has a low sensitivity for thoracic injuries25 and the more widespread use of CT among the trauma population could have resulted in an increased rate of detection of previously missed or underestimated injuries 24…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the patients included in this study was 43 (min-max 18-87) years, which was consistent with the literature, and the majority of the patients were male. [14][15][16][17][18][19][20] Previous reports have shown that mortality rates in patients with thoracic trauma are markedly high (up to 30%). [21] Emircan et al [22] reported a 22% mortality rate among patients presenting to the emergency department with thoracic trauma.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the emergent treatment of hemothorax with surgery or chest tube drainage, and because patients with flail chest often undergo surgical stabilization in the early period. A large study by Horst et al [19] included over 10 years of experience regarding patients with serious thoracic trauma. In that study, over those 10 years, there was a decrease in the requirement of those patients for urgent surgery, as well as in ventilation time, ICU stay length, and rate of respiratory failure development.…”
Section: Discussionmentioning
confidence: 99%
“…Burnside and McManus (2014) had presented a detailed summary on injury mechanisms and the severity of injury for BTT. Moreover, it is proved that RTA's are the principal cause for BTT and can be seen in Liman et al (2003), Shirley (2005) and Horst et al (2017). In fact, these mechanisms play an important role in the prediction of injury severity prior to radiological examination.…”
Section: Introductionmentioning
confidence: 99%